Highly-filled flowable composite in deep margin elevation: FEA study obtained from a microCT real model. Issue 4 (April 2022) - Baldi, Andrea; Scattina, Alessandro; Ferrero, Giorgio; Comba, Allegra; Alovisi, Mario; Pasqualini, Damiano; Peroni, Lorenzo; Muggeo, Matteo; Germanetti, Filippo; Scotti, Nicola
Abstract: Objectives: To evaluate shear stress (SS) and normal pressure (NP) at the tooth-restoration interface of highly-filled flowable resin composite applied to deep margin elevation technique through FEM analysis generated by a microCT scan. Methods: A reference maxillary molar with two class II cavities was prepared according to deep margin elevation protocol. A geometrical model was segmented from a micro-CT scan generating separate volumes of enamel, dentin and restorative materials. The 3D Finite Element (FE) model was subsequently built-up and an axial chewing load was simulated. Data concerning the tooth-restoration interface were analyzed in terms of SS and NP. Different materials and techniques were tested in order to evaluate the effects of the restorative material, the usage of a highly-filled flowable composite as liner and the substrate of the cervical area. Results: Both SS and NP presented similar distribution, but showed significant differences between tested materials. Composites showed more homogeneous behavior in stress distribution compared to ceramic. The use of a highly-filled flowable composite as liner on the cervical margin significantly reduced SS and NP on the cavity floor and the cervical margin area. Lastly, stress distribution in the cavity floor area varied according to the cervical margin substrate: enamel showed a protective role in stress distribution. Significance: Highly-filled flowable resin composites showed encouraging results when applied to deep margin elevation from an interfacial mechanical point of view. Further studies are needed to validate these data and to better define the role of cervical enamel in stress distribution. Highlights: Micro-CT can be used to create a realistic finite element model of the tooth-restoration complex. Highly-filled flowable resin reduced shear and normal pressure stresses on the cavity floor. Shear and normal pressure stresses presented similar distributions, being influenced by the different materials. Resin-based materials showed a more homogeneous behavior in stress distribution compared to ceramic.